(untitled) (Homoeopathy for All, 2024)
Energy is a capacity of doing work at spiritual as well as physical level. Homoeopathy treats patient as a whole on the basis of law of similia. From the ancient times to till today, moon is the important part of the human society and its days to day living. Luna is one of the natural sources derived Imponderabilia which have a diverse affinity for the human organism.